Correlation between the solar wind speed and the passage of poleward-moving auroral forms into the polar cap - Fasel, G. J.; Lee, L. C.; Lake, E.; Csonge, D.; Yonano, B.; Bradley, O.; Briggs, J.; Lee, S. H.; Mann, J.; Sigernes, F.; Lorentzen, D. (Frontiers in Astronomy and Space Sciences, 2024)
In 1961, Dungey suggested that magnetic reconnection occurs due to the solar-terrestrial interaction. The interplanetary magnetic field (IMF) is thought to merge with Earth's geomagnetic field (GMF). After the reconnection process the newly formed magnetic flux tube, consisting of both the IMF and GMF, moves anti-sunward. Poleward-moving auroral forms (PMAFs) are believed to be the ionospheric signatures of this process, which transfers magnetic flux from the dayside to the nightside. This paper looks at the connection between the solar wind speed and the motion of the PMAF as it moves from the auroral oval, anti-sunward, into the polar cap. PMAFs are identified using both the meridian scanning photometer (MSP) and colored all-sky camera (ASC). Once the PMAFs are identified, the PMAF-SLOPE, α α . The conclusions obtained from this statistical study are: (i) both the PMAF-SLOPE α v and α PMAF are highly correlated to the x v -component of the solar wind, increasing when x v increases and vice versa , (ii) PMAFs must be connected to both the IMF and GMF and are dragged anti-sunward, mostly by the x v -component of the solar wind, and (iii) PMAFs are indeed the ionospheric footprints of a newly formed magnetic flux tube, due to dayside magnetic reconnection, being transferred from the dayside to nightside.